2008
DOI: 10.5194/acpd-8-4811-2008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the volatility and production mechanisms of newly formed nitrate and water soluble organic aerosol in Mexico City

Abstract: Abstract. Measurements of atmospheric gases and fine particle chemistry were made in the Mexico City Metropolitan Area (MCMA) at a site ~30 km down wind of the city center. Ammonium nitrate (NH4NO3) dominated the inorganic aerosol fraction and showed a distinct diurnal signature characterized by rapid morning production and a rapid mid-day concentration decrease. The concentration increase was due to both secondary formation and entrainment from the free troposphere. A majority (approximately two-thirds) of th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
37
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 30 publications
12
37
0
Order By: Relevance
“…[17] These results are consistent with our previous findings that suggest a link between aerosol water and both WSOC p and secondary nitrate production [Hennigan et al, 2008]. In that study, the formation of relatively fresh ($2-3 hours) WSOC p in a region of predominantly anthropogenic emissions was also likely related to aerosol water, as was nitrate, in agreement with known nitrate thermodynamic properties.…”
Section: Resultssupporting
confidence: 82%
“…[17] These results are consistent with our previous findings that suggest a link between aerosol water and both WSOC p and secondary nitrate production [Hennigan et al, 2008]. In that study, the formation of relatively fresh ($2-3 hours) WSOC p in a region of predominantly anthropogenic emissions was also likely related to aerosol water, as was nitrate, in agreement with known nitrate thermodynamic properties.…”
Section: Resultssupporting
confidence: 82%
“…Assuming a particle diameter of 1 µm, the timescale for thermodynamic equilibrium of semi-volatile species was found to be 27±19 min for HNO 3 , 14±11 min for NH 3 , 18±15 min for NO 3 and 15±13 min for NH 4 , on average with a maximum during the night and early morning hours. These timescales are consistent with high-resolution measurements of aerosol nitrate (Hennigan et al, 2008), and with the observation that most of the PM 2.5 mass is in the submicron range . Changes in RH and temperature tend to affect equilibration over longer timescales than changes in aerosol precursor concentration.…”
Section: Discussionsupporting
confidence: 73%
“…3a, b) during the measurement period of 21-30 March (27±19 min for HNO 3 , 14±11 min for NH 3 , 18±15 min for NO 3 and 15±13 min for NH 4 , on average). These values are consistent with the detailed calculations of Wexler and Seinfeld (1992), more recent literature (Meng and Seinfeld, 1996;Dassios and Pandis, 1999;Cruz et al, 2000) and the high resolution measurements of nitrate by Hennigan et al (2008), which shows that measured nitrate lags about 30 min with respect to predictions based on bulk equilibrium. Furthermore, the equilibration timescale for NH 3 is close to that of NH 4 , and, the timescale of HNO 3 is close to that of NO 3 , despite that they include independent measurements of aerosol and gas-phase precursors; this strongly suggests consistency in the timescale analysis.…”
Section: Equilibrium Timescalesupporting
confidence: 79%
“…However, during the latter half of the daylight hours, the CCN-active fraction for all particle sizes approaches 100 %. κ CCNc for all particle sizes reaches a maximum within 1-2 h of local noon, suggesting that photochemical processes are dominant at that time, which is consistent with the peak in oxygenated organic aerosol mass (Aiken et al, 2009) and water soluble organic carbon mass (Hennigan et al, 2008) observed during the daytime at the T0 and T1 sites, respectively. New particle formation (NPF) events occurred frequently during MIRAGE 2006(Smith et al, 2008, as illustrated by the particle size distributions (Fig.…”
Section: Diurnal Changes In Aerosol Hygroscopicitysupporting
confidence: 61%